The susceptibility of adult schistosomes to immune attrition - A. M. Agnew; H. M. Murare; S. Navarrete Sandoval; N. de Jong; F. W. Krijer; A. M. Deelder; M. J. Doenhoff (Memorias do Instituto Oswaldo Cruz, 1992)
Mouse infection models are described that demonstrate reduction of egg production in Schistosoma haematobium infections and both worm loss and reduced fecundity in S. bovis infections. Neither phenomenum could be shown in S. mansoni infected mice. The immunological basis for these anti-adult responses was inferred by comparison with infections in T-cell deprived mice and by the serum transfer of the ability to reduce a S. bovis worm burden into immunocompromised hosts. Vaccination with irradiation attenuated parasites was also shown to have consequences for the adults of a challenge infections of S. haematobium and S. bovis specifically. Prior vaccination resulted in an abrogation of the anti-fecundity and adult worm elimination that occurred in non-vaccinated similary infected mice. hese models are being used to define the targets and mechanisms involved in anti-adult attrition. A serological assay, quantitation of a circulating antigen (CAA) has been assessed for its ability to measure worm burdens of different species of schistosome in mice. This assay will be used to question whether anti-adult immunity contributes to the pattern of infection with S. mansoni and S. haematobium in man.